Role of Toll-Like Receptor 4 on Lupus Lung Injury and Atherosclerosis in LPS-Challenge ApoE−/− Mice. (15th September 2013) - Ni, Jing-qin; Ouyang, Qiufang; Lin, Ling; Huang, Ziyang; Lu, Huixia; Chen, Xiaoqing; Lin, Huili; Wang, Zhenhua; Xu, Dongming; Zhang, Yun
Abstract : To investigate the pathologic mechanisms of toll-like receptor 4 (TLR4) in lung injury and atherosclerosis, ApoE −/− or wild-type mice were intraperitoneally administered saline, lipopolysaccharides (LPS), or LPS plus TAK-242 (TLR4 inhibitor), respectively, twice a week for 4 weeks. Serum autoantibody of antinuclear antibody (ANA), anti-double-stranded DNA (anti-dsDNA), and cytokines of interferon-gamma (IFN- γ ), tumor necrosis factor (TNF- α ), and interleukin-1 (IL-1 β ) were assessed by ELISA. Hematoxylin and eosin (HE) and Perl's stains for lung pathomorphology as well as HE staining for atherosclerosis were employed. TLR4 in macrophages was detected by double immunofluorescent staining. While protein expressions of TLR4, nuclear factor-kappa B p65 (NF- κ B p65), and B cell activating factor belonging to the TNF family (BAFF) were examined by immunohistochemistry. We found that serum autoantibody (ANA and anti-dsDNA), cytokines (IFN- γ, TNF- α, IL-1 β ), lung inflammation, and intima-media thickness in brachiocephalic artery were obviously increased after LPS challenge in both genotypes, but to a lesser extent in wild-type strains. And those alterations were alleviated by coadministration of LPS and TAK-242. Mechanistically, upregulation of TLR4, NF- κ b, and BAFF was involved. We concluded that TLR4/NF- κ b/BAFF in macrophages might be a possible common autoimmune pathway that caused lung injury and atherosclerosis. TLR4 signal will be a therapeutic target in atherosclerosis and immune-mediated lung injury.